Educational Collaboration Between Russian-Born US Physicians and Russian Oncology Trainees in Evidence-Based Medicine: The Higher School of Oncology. (2021) - Baron, Ekaterina; Sittig, Michelle; Kotov, Maxim; Fomintsev, Ilya; Gushchin, Vadim
Abstract : PURPOSE: The 2-year Russian oncology residency focuses on diagnosis and treatment of malignancies but lacks evidence-based medicine (EBM) and patient communication skills (PCS) training. To overcome these educational disparities, the 5-year national program, the Higher School of Oncology (HSO), involving Russian expatriate physicians trained in the United States was established. METHODS: A retrospective study was conducted. Highly motivated oncology residents were enrolled in the program through the three-step selection process. US-trained Russian expatriate physicians acted as mentors. EBM skills were taught through weekly online journal clubs and clinical case presentations. PCS training included live seminars and simulations after journal clubs. EBM knowledge was assessed using Fresno test among newly enrolled and postgraduate year (PGY) 2-5 HSO residents. PCS were evaluated via simulation exam including two clinical scenarios (maximum score 100 each) among 17 PGY2 HSO residents and seven non-HSO trainees. RESULTS: Overall, 54 residents were enrolled over 5 years (8-13 annually); four were released from the program. The mean age was 24 ± 1 years, and 56% were females. Median scores of Fresno test were significantly higher among PGY 2-4 HSO residents compared with newly enrolled participants: 111 (IQR, 71-128) versus 68 (IQR, 42-84), P = .042; moreover, performance correlated with year of program participation (rs = 0.5; P < .0001). PCS assessment score was significantly higher among HSO residents than non-HSO trainees: 71 (IQR, 58-84) versus 15 (IQR, 10-30) for scenario number 1 ( P < .0001) and 78 (IQR, 71-85) versus 22 (IQR, 4-58) for scenario number 2 ( P = .005), respectively. CONCLUSION: The involvement of Western-trained expatriates in remote education improves EBM and PCS among oncology trainees from their home country. This strategy can be useful in overcoming global medical education disparities in other specialties and in countries facing similar challenges.